Colonial Intimacies: Constellations of Property and Kinship in German Colonial (After)Lives - Vögele, Hannah (Kvinder, Køn & Forskning, 2022)
This paper contends that relations of property and propriety of “western modernity” engender and articulate different forms of violence, crucially including sexualised violence. Upholding anti-colonial feminist approaches, this paper takes seriously the need to trace how modern ways of relating are intimately connected to colonial modes of dispossession and propertisation. Therefore, I draw on historical resources and present a constellation history with fragments from relations of intimacy in German colonial rule. This shows how hegemonic family relations and marriage laws were used to control access to land and resources, as well as workers and their bodies. Logics of imperial intervention in sexuality and the use of sexualised violence extend beyond this specific spatio-temporal context into the present. This highlights how categories of race, gender and sexuality develop with, through and for proprietary relations. The ambiguous role of white women vis-à-vis colonial relations of ownership reinforces a critique of limited approaches of liberal feminism and stresses the importance of anti-colonial organizing against violence.